The Supportive Role of Insulin-Like Growth Factor-I in the Differentiation of Murine Mesenchymal Stem Cells into Corneal-Like Cells - Trosan, Peter; Javorkova, Eliska; Zajicova, Alena; Hajkova, Michaela; Hermankova, Barbora; Kossl, Jan; Krulova, Magdalena; Holan, Vladimir (Stem cells and development, 2016)
This study was focused on characterizing the differentiation of bone marrow-derived mesenchymal stem cells (MSCs) into corneal-like cells. Mouse MSCs were isolated from the bone marrow, grown in cell culture for 3 weeks, and purified using a magnetic activated cell sorter. Purified MSCs were cultured with an extract prepared from excised corneas and in the presence or absence of insulin-like growth factor-I (IGF-I). Analysis by quantitative real-time polymerase chain reaction showed that the expression of corneal specific markers, such as cytokeratin 12 (K12), keratocan, and lumican, was already induced after a 3-day cultivation and gradually increased during the 10-day incubation of MSCs with the extract. The presence of IGF-I significantly increased differentiation. Immunofluorescence analysis of differentiated MSCs showed positive results for the K12 protein. The morphology of the differentiated cells and the expression of cell surface markers CD45, CD11b, CD73, CD44, and CD105 were comparable in the control and differentiated MSCs. Proliferative activity was even higher in differentiated cells than in untreated MSCs. Both untreated and differentiated MSCs inhibited the production of interleukin-2 and interferon-γ in spleen cells stimulated with Concanavalin A. The results thus show that MSCs cultured in the presence of corneal extract and IGF-I efficiently differentiate into corneal-like cells. The differentiated cells possess characteristics of corneal epithelial cells and keratocytes, while at the same time maintaining MSC properties.
Keywords: Animals; Insulin-Like Growth Factor I; proliferace buněk; tvar buňky; Female; mezenchymální kmenové buňky; biologické markery; Biomarkers; ženské pohlaví; rohovka; Cornea; buněčná diferenciace; Mice, Inbred BALB C; Cell Shape; Mesenchymal Stem Cells; regulace genové exprese; insulinu podobný růstový faktor I; Male; myši inbrední BALB C; Immunosuppression Therapy; Cell Proliferation; Cell Differentiation; Gene Expression Regulation; zvířata; mužské pohlaví; imunosupresivní léčba